Periodical and regional change of particulate matter and CO2 concentration in Misurata - Elsunousi, Ahlam Ahmed Mohamed; Sevik, Hakan; Cetin, Mehmet; Özel, Halil Barış; Özel, Handan Ucun (Springer Science and Business Media LLC, 2021)
Today, environmental pollution, air pollution in particular, is among the most important problems in the world. Air pollution, which has become a global issue, is estimated to cause the death of around 1 in 8 people worldwide. Due to the significance of air pollution, all components of air pollution are of great importance for human health, and thus the studies on air pollution are highly important, especially in areas with high population density. In this study, it was aimed to determine the regional and periodic change of CO2 and particulate matter pollution in the city of Misurata, one of the important cities of Libya. The study was conducted in the city centre of Misurata, and the measurements were made once in every three days between November and February at 7 different locations selected in the city centre. As a result of the measurements made, the changes in the pollution parameters were evaluated on the basis of zones and months. As a result of the study, the cleanest areas were found to be the industrial area (B3) located in the east of the city and the zone (B4), where the Al-Swehli farm was located, while the dirtiest areas were found to be the main street (B1 and B2) in the city centre and the city centre, in general. In terms of months, the lowest CO2 values were obtained in January, and the highest value was in February, whereas the lowest particulate matter values were obtained in January and the highest values in December.
Keywords: Air Pollutants; Management, Monitoring, Policy and Law; Carbon Dioxide; Air Pollution; Humans; Co2; Particulate Matter; Misurata; Environmental Monitoring; 6. Clean water; 12. Responsible consumption; 3. Good health; 13. Climate action; 11. Sustainability